Aplikasi Marketplace Lelang Berbasis Android - Bravery Victorian Minggara Putra; Lily Puspa Dewi; Anita Nathania Purbowo (Jurnal Infra, 2019)
One way someone "sells" the item is through an online auction. There are already many online auction sites on the internet. However, most auction sites only cover certain categories of goods, such as motorized vehicles or land. In addition to auction sites, there are also several communities that conduct auctions through social media. However, auction using social media also has it shortcomings, such as an ambiguous system because there is no dedicated system on social media specifically made for auctioning.To answer this problem, an application designed specifically for conducting online auctions which is not limited by certain categories. The application can be used as a medium of trading for its users, and also can accommodate many users to conduct auctions in accordance with the system and the rules that apply in general.The results of the tests indicate that the application can receive every auction data, bid, and transaction that is carried out. The application can also connect multiple users in the auction and transaction process.